Gut-lung immunometabolic crosstalk in sepsis: from microbiota to respiratory failure - Li, Qixiu; Song, Xi-Cheng; Li, Kefeng; Wang, Jing (Frontiers in Medicine, 2025)
Sepsis is a systemic immune-metabolic disorder syndrome caused by infection, in which gut microbiota dysbiosis plays a central role in the occurrence and development of multi-organ dysfunction. This paper systematically elaborates on the bidirectional regulatory mechanism of the “gut-lung axis” in sepsis. Gut microbiota dysregulation damages the gut barrier function, reduces the production of short-chain fatty acids (SCFAs), and increases endotoxin translocation. Subsequently, it activates alveolar macrophage polarization, promotes the formation of neutrophil extracellular traps (NETs), and leads to an imbalance in the Treg/Th17 cell ratio, ultimately exacerbating the pathological process of acute lung injury (ALI) or acute respiratory distress syndrome (ARDS). Conversely, the pulmonary inflammatory response can also aggravate gut barrier damage through circulating inflammatory mediators, forming a vicious cycle. Mechanistically, HIF-1α, mTOR, and Sirtuins do not act in isolation. Instead, they jointly regulate the metabolic fate of immune cells through spatiotemporally dynamic interactions. During the evolution of sepsis, these signals exhibit opposite regulatory polarities during the hyper-inflammatory phase and the immunosuppressive phase, and mitochondrial dysfunction and oxidative stress further amplify the inflammatory cascade reaction. Preclinical research evidence shows that microbiota-based intervention measures (including probiotic preparations, fecal microbiota transplantation, and SCFA supplementation) and vagus nerve electrical stimulation can effectively alleviate sepsis-related lung injury and improve prognosis, but there is significant individual heterogeneity in their therapeutic effects. Future research should not be restricted to descriptive associations. Instead, it is essential to conduct in-depth analyses of the specific logic of the aforementioned signaling networks in terms of cell types, subcellular compartments, and disease course timings, and clarify their context-dependent controversies to promote the transformation of mechanistic understanding into precision treatment. Meanwhile, research efforts should focus on constructing a multi-omics dynamic biomarker system integrating metagenomics, metabolomics, and immunophenotyping analysis and designing clinical trials through precise patient stratification to facilitate the clinical translation of individualized treatment strategies based on gut-lung axis regulation.